2019
DOI: 10.3390/jcm8010108
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Molecular Profile of Lung Cancer: New Strategies for the Early Detection and Prognostic Stratification

Abstract: Recent advances in radiological imaging and genomic analysis are profoundly changing the way to manage lung cancer patients. Screening programs which couple lung cancer risk prediction models and low-dose computed tomography (LDCT) recently showed their effectiveness in the early diagnosis of lung tumors. In addition, the emerging field of radiomics is revolutionizing the approach to handle medical images, i.e., from a “simple” visual inspection to a high-throughput analysis of hundreds of quantitative feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…Nowadays, the advent of more sophisticated and precise bioinformatic tools and computational approaches has sped up the identification of novel diagnostic and prognostic cancer biomarkers, either focused on proteins, coding transcripts, epigenome modifications or non-coding transcripts [ 14 , 15 ]. In lung cancer, in particular, the differential expression of miRNAs allowed the development of innovative and promising cancer biomarkers [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the advent of more sophisticated and precise bioinformatic tools and computational approaches has sped up the identification of novel diagnostic and prognostic cancer biomarkers, either focused on proteins, coding transcripts, epigenome modifications or non-coding transcripts [ 14 , 15 ]. In lung cancer, in particular, the differential expression of miRNAs allowed the development of innovative and promising cancer biomarkers [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The National Comprehensive Cancer Network Guidelines recommends testing a panel of genes for NSCLC, which consists of epidermal growth factor ( EGFR ) mutations, anapestic lymphoma kinase ( ALK ) rearrangements, and c-ros oncogene 1 ( ROS1 ) rearrangements. These biomarkers are considered the “must-tests” biomarkers in lung cancer patient diagnosis and are analyzed by single-gene assays such as PCR, immunohistochemistry (IHC), and FISH [ 20 , 55 , 56 , 57 , 58 , 59 , 60 ]. Sanger sequencing, qPCR, ddPCR, IHC, and FISH are regarded as the gold standard techniques of molecular analysis in clinical practice, while tumor-only sequencing, matched-tumor, and normal-tissue sequencing are the gold standards in somatic mutation detection [ 18 , 61 ].…”
Section: Advancement Of Molecular Strategies and Techniques Used Tmentioning
confidence: 99%
“…An example is a new nomenclature for the adenocarcinoma subtype proposed by The Cancer Genome Atlas Consortium (TCGA). The TCGA′s classification integrated the transcriptional subtypes with the histopathological, anatomic, and mutational categorizations and consists of three subtypes that are characterized by specific genetic alterations ( Table 4 ) [ 56 ].…”
Section: Lung Cancer Genetic Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, serum metabolites and lipids have emerged as another class of potential biomarkers in lung cancer [ 16 , 17 ]. Several other review papers could be suggested that cover this well-researched field [ 11 , 12 , 13 , 18 , 19 , 20 , 21 ]. However, though numerous biomarker candidates have been proposed only a few of them have been positively validated in the proper clinical settings.…”
Section: Introductionmentioning
confidence: 99%